Discovery of HLA‐DRB1*03:20 allele in a Taiwanese volunteer hematopoietic stem cell donor and the probable HLA‐A, ‐B, ‐C and ‐DRB1 haplotype in association with DRB1*03:20. (25th August 2012) - Yang, K. L.; Lee, S. K.; Yang, S. Y.; Kao, R. H.; Lin, C. L.; Lin, P. Y.
Summary The allele HLA‐DRB1*03:20, a variant of DRB1*03, was first reported to the IMGT HLA database in April 2001 without indication on the ethnicity of the blood donor (Cell ID: HC 125775). We found a Taiwanese volunteer hematopoietic stem cell donor carries DRB1*03:20 by a sequence‐based typing (SBT) method. The DNA sequence of DRB1*03:20 is identical to the sequence of DRB1*03:01:01 in exon 2, except a nucleotide substitution at position 341(T→C) (GTT→GCT at codon 85). The nucleotide replacement produced an amino acid variation at residue 85 (V→A). We hypothesize that DRB1*03:20 was probably derived from DRB1*03:01:01 via a nucleotide point mutation event. The probable HLA haplotype in association with DRB1*03:20 was deduced as A*11:02‐B*58:01‐C*07:02‐DRB1*03:20. We here report the Taiwanese/Chinese ethnicity of DRB1*03:20.